If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -6) + -10 = 2x Reorder the terms: 4(-6 + x) + -10 = 2x (-6 * 4 + x * 4) + -10 = 2x (-24 + 4x) + -10 = 2x Reorder the terms: -24 + -10 + 4x = 2x Combine like terms: -24 + -10 = -34 -34 + 4x = 2x Solving -34 + 4x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -34 + 4x + -2x = 2x + -2x Combine like terms: 4x + -2x = 2x -34 + 2x = 2x + -2x Combine like terms: 2x + -2x = 0 -34 + 2x = 0 Add '34' to each side of the equation. -34 + 34 + 2x = 0 + 34 Combine like terms: -34 + 34 = 0 0 + 2x = 0 + 34 2x = 0 + 34 Combine like terms: 0 + 34 = 34 2x = 34 Divide each side by '2'. x = 17 Simplifying x = 17
| b=11-a | | 2(x-4)-6=-6(-2x+4)-6x | | 6r+5=55 | | k+3=6+k | | 30+(.0825*30)+(15%*30)= | | 6(y+2)=-2(8y-7)+6y | | -26+26=-15p-10p | | 11x-4=5x+9 | | x*12=-2 | | X+3(4)=48 | | 3x+10=3x+4+1 | | 2(x-1)-3x=8 | | 8-2x=2x-5x | | 1x+3(4)=48 | | 9(-10)+160= | | -6h+2=-46 | | x+7=-3+3x | | .60x+.30(90)=.50(x+90) | | 6=18b | | 3x+15=12b-3b | | x*-5=10 | | 16t^2-128+400=0 | | 2a+24-3a=5a | | 8p-4=7p-2 | | n^2-34n-251=0 | | t^2-8+25=0 | | 1-m=1-m | | 16.28+8=100 | | -4n+2=-13-7n | | x^7-5x+6=0 | | 13x+23y=-5 | | -6+4p=5p-4 |